2008
DOI: 10.1007/s12221-008-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and characterization of conductive poly(ethylene terephthalate)/polyaniline composite fibers using benzoyl peroxide

Abstract: Conductive polyaniline (PAn)/poly(ethylene terephthalate) (PET) composite fibers were prepared by chemical polymerization of aniline in the presence of PET fibers using benzoyl peroxide (Bz 2 O 2 ) in organic solvent/aqueous hydrochloric acid mixtures. The effects of polymerization conditions such as organic solvent/water ratio, oxidant, aniline and hydrochloric acid concentrations and temperature were investigated on the amount of PAn deposited on PET fiber and the electrical surface resistance of composite f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Jung et al27 and Yang et al 17 reported PEDOT‐coated PET fabrics and their possible use in EMI shielding and heat generation applications. PET based conductive fibers have also been produced by coating them with PANI and PPy 28, 29…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al27 and Yang et al 17 reported PEDOT‐coated PET fabrics and their possible use in EMI shielding and heat generation applications. PET based conductive fibers have also been produced by coating them with PANI and PPy 28, 29…”
Section: Introductionmentioning
confidence: 99%
“…Although the polymerization conditions were changed, the highest PAn–PTh content (%) of composite fibers was 2% and the lowest surface resistivity was measured as 24 MΩ/cm 2 . This resistivity value was higher than that from PAn/PET and PTh/PET conductive composite fibers reported in our previous studies; consequently, the PET samples were swollen in dichloromethane which is known as a swelling agent for PET fibers, at boiling temperature for 2 h, and these fibers were used in experiments.…”
Section: Resultsmentioning
confidence: 57%
“…Three types of materials have been explored for the fabrication of high-conductivity textiles: polymer-based, carbon-based, and metallic materials [1]. The electronic textiles can be achieved through the introducing of conductive polymers such as polyaniline (PANI) [9,10], polypyrrole (PPy) [11], polythiophene (PT) [12]; also, via electrochemical, or chemical polymerization processes [13,14]. PANI has been defined to be the first dispersible essentially conductive polymer readily accessible and stable in ambient conditions [15].…”
Section: Introductionmentioning
confidence: 99%